28th Annual APRN Legislative Update: Advancements continue for APRN practice. Issue 1 (16th January 2016) - Phillips, Susanne J.
Abstract : Abstract: The Annual Legislative Update discusses the legislative accomplishments in the areas of practice authority, reimbursement, and prescriptive authority that have the most impact on nurse practitioners and other advanced practice nurses across the country. Abstract : This year's review and annual advanced practice registered nurse legislative update heralds significant state legislative accomplishments in the areas of APRN practice authority, reimbursement, and prescriptive authority.